Programa ensino médio inovador : a recontextualização curricular do ensino de ciências da natureza e matemática - Correia, Wilian Rodrigues (2014)
This paper presents an investigation on the curriculum of the teaching of Natural Sciences and Mathematics in a State School of Mato Grosso, which participates in the ProEMI (ProEMI) of the federal government (MEC). It also aims to understand how the process of (re)signification of the curriculum of the teaching of Natural Sciences and Mathematics has been happening, based on the political proposal for curricular restructuring of the ProEMI guidance document, and on the perspectives of teachers and management staff, establishing a relationship between what is proposed in the guidance document, Political Pedagogical Project (PPP) and the pedagogical practices of the teaching of Natural Sciences and Mathematics. Because this is about high school, the description of the structure conferred by the Law of Guidelines and Basis of National Education (Lei 9.394/96) was considered, using the National Curricular Parameters for high school, PCNem and the National Curriculum Guidelines for Secondary Education, DCNem. This is a qualitative approach, with elements of a case study in which, the first contacts with the locus of research were upon submission of the proposal to the management team of the school. In the preliminary phase of data collection, questionnaires, analysis of curriculum, analysis of the curriculum restructuring project (PRC) and documental analysis of the PPP were conducted, which allowed the development of the schools’ record and the understanding of the curriculum proposal, in addition to providing for the development of a semi-structured interview, with seven people in the school community, five teachers of the areas of Natural Sciences, Mathematics and its technologies, one articulator of the ProEMI and one educational coordinator. The data analysis is presented based on the triangulation of the information obtained in reading of the documents cited above and in the systematization of the interviews, for which some analysis criteria were established, such as: the times and spaces, the pedagogical practices for teaching of Sciences, the planning of activities in the teaching of Sciences, the methodologies and teaching strategies used by the teacher after the school’s insertion in ProEMI. The partial results suggest that the Program has the objective of supporting innovative teaching practices in schools, the encouragement of youth participation in particular. In fact, there is no revolutionary proposal. Perhaps the central focus of the program, in regard to "innovation", is to offer 20% of elective workload for youth leadership, which does not occur in the school studied. Another important fact is six hundred hours increase in the three years of high school. It also shows that the curriculum of the teaching of Natural Sciences and Mathematics still has traditional features, with little change, even after the guidelines of the Program.